Desenvolvimento de líderes no segmento da construção civil - Sasso, Marciano (Universidade do Vale do Rio dos Sinos, 2016)
In companies of the construction industry, especially in technical areas such as engineering, work and even commercial, in which most functions need to be developed by engineers with technical expertise, the division between expert and manager can be superimposed. But being manager is not always desire for a technical engineer who finds his personal recognition on the technical expertise of engineering. In the civil construction companies, vacancies for management tend to be more crowded, and to conquer them, if required, some specific skills that not everyone likes or feel motivated to develop them; have vacancies in the technical area exist in greater quantity, but in technical career can take longer for a professional to become manager or director, and not to lose these professionals with technical profile, some companies develop a parallel career also known as career Y. Not always the professional envisions a career management, then companies need to understand and recognize the professional if it is motivated in technical function or management. This study sought to identify and analyze the elements necessary for the preparation and selection of professionals to work as managers in the construction sector in a national institution. Therefore, there was exploratory research, with the strategy case study increased with the learning acquired during the MBA and bibliographic research qualitative interviews, semi-structured, with seven managers engineers working in the construction industry were held. The results highlight the need for systematization and reflection of professionals who decide to take up positions as a manager, either by themselves as professionals by the company.
Keywords: Gestor; Preparação; Desenvolvimento; Potencial; Construção civil; Manager; Preparation; Development; Potential; Construction